Species Diversity and Endemicity in the Angolan Leguminosae Flora - Catarino, Silvia; Goyder, David; Darbyshire, Iain; Costa, Esperança; Figueira, Rui; Duarte, Maria Cristina; Romeiras, Maria Manuel (Frontiers in Ecology and Evolution, 2022)
Angola has a great diversity of species and ecosystems and a high level of endemism. However, knowledge of the native flora remains very incomplete and outdated. Leguminosae is the largest family in the country, including many species which are of local or more regional economic importance. Based on an extensive review of bibliographic sources, natural history collections and online databases, the checklist of Angolan Leguminosae plants was updated, including data on their native distribution, conservation status and principal uses. The endemic taxa were the subject of additional investigation, including the main habitat, the number of collections preserved in herbaria and the locality of the first collection. We identified 953 Leguminosae taxa occurring in Angola, of which 165 are endemic to the country. Among the 180 genera found, Crotalaria (136) and Indigofera (96) have the highest number of taxa. Almost half of the studied species have important applications, mainly in traditional medicine (383), forage (264), timber (187) and food (120). Nevertheless, only 27.7% have been assessed according to the IUCN Red List and 10 species are classified as threatened. Thirty-three endemics are known only from the type specimen, revealing the lack of knowledge on these species and the need for further field research. More than 30 type specimens were collected in the Serra da Chela, which highlights the importance of this region for biodiversity conservation.